Exfoliated graphdiyne for the electroless deposition of Au nanoparticles with high catalytic activity. Issue 2 (12th November 2020) - Gao, Yan; Li, Changwei; Yi, Wei; Fei, Junjie; Yi, Lanhua; Yu, Ping; Mao, Lanqun
Abstract : Graphdiyne (GDY), a novel two-dimensional (2D) carbon material with sp- and sp 2 -hybridized carbon atoms, has earned a lot of attention in recent years. Abstract : Graphdiyne (GDY), a novel two-dimensional (2D) carbon material with sp- and sp 2 -hybridized carbon atoms, has earned a lot of attention in recent years. Owing to its low reduction potential and highly conjugated electronic structure, it can be used as a reducing agent and stabilizer for the electroless deposition of highly dispersed Au nanoparticles. In this paper, we observe that exfoliated GDY (eGDY), the exfoliation of bulk GDY into single- or few-layered GDY in aqueous solution, can be used as an excellent substrate for the electroless deposition of very small Au nanoparticles to form a Au/eGDY nanocomposite that exhibits higher catalytic performance for the reduction of 4-nitrophenol. The higher catalytic performance is considered to arise from the high specific surface area of eGDY and the electroless deposition of active metal catalysts with eGDY as the support. Our results inspired the present investigation into the use of eGDY for the development of highly efficient catalysts.